Engineering Host Microbiome for Crop Improvement and Sustainable Agriculture - Kaul, Sanjana; Choudhary, Malvi; Gupta, Suruchi; Dhar, Manoj K. (Frontiers in Microbiology, 2021)
Dynamic consortium of microbial communities (bacteria, fungi, protists, viruses, and nematodes) colonizing multiple tissue types and coevolving conclusively with the host plant is designated as a plant microbiome. The interplay between plant and its microbial mutualists supports several agronomic functions, establishing its crucial role in plant beneficial activities. Deeper functional and mechanistic understanding of plant-microbial ecosystems will render many “ecosystem services” by emulating symbiotic interactions between plants, soil, and microbes for enhanced productivity and sustainability. Therefore, microbiome engineering represents an emerging biotechnological tool to directly add, remove, or modify properties of microbial communities for higher specificity and efficacy. The main goal of microbiome engineering is enhancement of plant functions such as biotic/abiotic stresses, plant fitness and productivities, etc. Various ecological-, biochemical-, and molecular-based approaches have come up as a new paradigm for disentangling many microbiome-based agromanagement hurdles. Furthermore, multidisciplinary approaches provide a predictive framework in achieving a reliable and sustainably engineered plant-microbiome for stress physiology, nutrient recycling, and high-yielding disease-resistant genotypes.